Open‐Circuit Ultrafast Generation of Nanoscopic Toroidal Moments: The Swift Phase Generator. Issue 1 (28th December 2018) - Wätzel, Jonas; Berakdar, Jamal
Abstract: Efficient and flexible schemes for a swift, field‐free control of the phase in quantum devices have far‐reaching impact on energy‐saving operation of quantum computing, data storage, and sensoring nanodevices. A novel approach for an ultrafast generation of a field‐free vector potential that is tunable in duration, sign, and magnitude, allowing to impart non‐invasive, spatiotemporally controlled changes to the quantum nature of nanosystems is reported. The method relies on triggering a steady‐state toroidal moment in a donut‐shaped nanostructure that serves as a vector‐potential generator and quantum phase modulator. Irradiated by moderately intense, few cycle THz pulses with appropriately shaped polarization states, the nano donut is brought to a steady‐state where a nearby object does not experience electric or magnetic fields but feels the photo‐generated vector potential. Designing the time structure of the driving THz pulses allows for launching picosecond trains of vector potentials which is the key for a contact‐free optimal control of quantum coherent states. This research can trigger a new class of ultrafast quantum devices operated and switched in an energy‐efficient, contact and field‐free manner, enabling new techniques for use in quantum information, magnetic nanostructures, and superconducting tunnel junctions as well as in toroidally ordered systems and multiferroics. Abstract : The theory predicts the generation of localized toroidal moments in nanostructures upon irradiation by polarization‐tailored THz pulses. No electric or magnetic fields are produced, but only a gauge‐invariant vector potential that couples and controls phase‐sensitive devices such as Josephson or tunnel junctions. The setup serves as an ultrafast phase generator and modulator useful for performing pump–probe phase modulation in quantum matter.